Species-specific allostatic load indices fail to identify predictors or health outcomes of higher allostatic load in zoo-housed chimpanzees (Pan troglodytes) and bonobos (Pan paniscus) - Edes, Ashley N.; Brand, Colin M.; Brown, Janine L.; Edwards, Katie L. (Frontiers in Conservation Science, 2025)
IntroductionWhile the potential for using allostatic load to better understand animal wellbeing is well recognized in the zoo and conservation community, existing applications of allostatic load in wildlife have not been as promising as hoped given the robust results seen in human research. MethodsThrough a retrospective study of zoo-housed chimpanzees and bonobos, we 1) developed a species-specific allostatic load index (ALI), 2) analyzed whether allostatic load scores were associated with multiple predictor variables (e.g., age, sex, origin) or predicted health outcomes, and 3) compared ALIs with another multi-biomarker method, Mahalanobis distance (DM).ResultsOnly one predictor variable showed a significant association with allostatic load, with male chimpanzees having lower allostatic load than females. In contrast, older age predicted DM in chimpanzees, male bonobos had significantly lower DM than females, and zoo-born individuals of both species had significantly lower DM than wild-caught conspecifics. Age and sex alone better predicted all-cause morbidity and cardiac disease compared to models containing ALIs, and models for mortality risk were not substantially improved by the inclusion of an ALI. ALIs were compared to DM using Akaike’s information criterion (AIC) for chimpanzees and AIC adjusted for small sample sizes (AICc) for bonobos. In both species, DM models had the lowest AIC/AICc for all health outcomes compared to the ALI models, indicating improved performance of DM over allostatic load for predicting health outcomes.DiscussionOverall, ALIs poorly measure wellbeing and health outcomes in chimpanzees and bonobos; therefore, other multi-biomarker methods like DM may be more useful in nonhuman primates and other taxa.